Human Pharmacology of Cefotaxime (HR 756), a New Cephalosporin - Lüthy, Ruedi (1979)
Cefotaxime (HR 756) is a new semisynthetic parenteral cephalosporin with exceptional activity against gram-negative organisms and considerable stability against their β-lactamases. To study its pharmacokinetic properties, 0.5-, 1-, and 2-g doses were administered to each of six volunteers intravenously over 15 min, followed by a sustaining infusions of 0.5, 1, and 2 g/h, respectively, for 3 consecutive hours. The loading doses produced mean peak levels of 41, 93, and 160 μg/ml, and mean steady-state serum concentrations were 27, 64, and 138 μg/ml, respectively. The mean terminal half-life was 75 ± 7 min. The total volume of distribution averaged 0.22 ± 0.03 liters/kg of body weight. Total body and renal clearances were 232 ± 30 and 145 ± 24 ml/min per 1.73 m(2), respectively; 63 ± 9% of the administered dose was excreted through the kidneys in 24 h. To determine the effect of cefotaxime on the renal tubules, urinary alanine aminopeptidase excretion was measured before, during, and after the infusions. It remained within the normal range in all instances; however, 48 ± 14% of the total daily alanine aminopeptidase output was recovered during the infusion period. Side effects were dose related and included fatigue, loose stools, and night sweats. No significant changes in hematology, serum chemistry, or urinalysis were recorded.